Proposed Decision on Article IV Consultation Cycles. (Policy Papers; Policy Paper ;, 2010)
The proposed Decision seeks to implement the staff's proposals related to Article IV consultation cycles in Review of the Fund's Mandate-Follow-Up on Modernizing Surveillance, which were endorsed in principle by the Executive Board on September 1, 2010. The goal is to provide for greater flexibility in consultation cycles and simplify the rules governing consultation cycles for members under a Fund arrangement or Policy Support Instrument (PSI).